Evaluation of serum ceruloplasmin, copper, iron and Vit.C levels inWomen using oral contraceptive pills in Tikrit city - A.Abed, Saifaldin; R.Mahmood, Ayhan; Riffat Sarhat, Entedhar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Oral contraceptive steroids are used by an estimated 60 to 70 million women worldwide. Over the past 20 years there have been both case reports and clinical studies on the topic of drug interactions with these agents. The use of oral contraceptives has been consistently associated with decreased levels of the activity of many enzymes, and Vitamin C. The main transporter of copper, a2-globulin ceruloplasmin which is a multifunctional enzyme. The present study was conducted in Family planning in Tikrit Teaching Hospital in Tikrit province, Serum ceruloplasmin, copper, vitamin C, and iron levels were estimated in 54 women who were using oral contraceptives for at least I year. The mean age of women was (32.08 years vs. 27.04 years of control). The serum level of ceruloplasmin (Cp) as antioxidant protein was significantly high in comparison to control group (mean 40.5 mg/dl vs. 33.28 mg/dl, Pof serum copper in women were using contraceptive (17.03 J.!MIL) is significantly higher (Pvitamin C values in women using contraceptives were significantly lower than control group (P<0.05), the mean of vitamin C value was 3.452 -tM/L vs. 6.534 -tM/L of control. The mean value of serum iron in women were using contraception (8.642 tM/L) which is less significantly (P(17.603 -tM/L).